From policy intent to climate-smart implementation: developing the Saudi climate-smart social housing governance model (S-CSHGM) - Baesse, Samer Sami (Frontiers in Built Environment, 2026)
IntroductionSaudi Arabia’s Vision 2030 positions social and affordable housing as a strategic lever for climate-smart urban development. However, despite advanced regulatory instruments such as the Mostadam Green Building Rating System and Saudi Building Code (SBC 601), a persistent implementation gap raises critical questions about how governance arrangements shape actual sustainability outcomes in energy use, comfort, and water efficiency.MethodsGuided by institutional theory and the accountability trap concept, this study develops a six-factor analytical model of the enabling environment for sustainable, AI-ready social housing. A qualitative, multi-method approach triangulates: (i) systematic analysis of 42 national policy documents (2016–2025); (ii) a two-round Delphi survey with 23 experts; and (iii) structured benchmarking against Singapore’s Green Mark, Abu Dhabi’s Estidama, and Qatar’s Global Sustainability Assessment System.ResultsThe analysis reveals pronounced institutional voids and accountability traps. While sustainability is strongly embedded in formal regulations, responsibilities for post-occupancy and digital performance are diffuse; procurement and finance remain weakly linked to lifecycle outcomes; and fragmented data systems limit the use of smart-building and AI-enabled tools. Delphi findings prioritize performance-linked procurement, unified housing-performance data platforms, mandatory post-occupancy evaluation, and green finance instruments—practices aligned with international benchmarks.DiscussionThe study proposes the Saudi Climate-Smart Social Housing Governance Model (S-CSHGM), a four-pillar, AI-ready framework designed to realign roles, incentives, digital infrastructures, and feedback loops. This advances theory by operationalizing institutional and accountability concepts into a measurable governance model and provides a concrete roadmap to link Vision 2030 housing ambitions with verifiable, data-driven sustainability performance in Saudi Arabia’s built environment.